2019
DOI: 10.1111/ejss.12847
|View full text |Cite
|
Sign up to set email alerts
|

A review of the abundance, behaviour and detection of clostridial pathogens in agricultural soils

Abstract: The soil is a reservoir for various clostridial pathogens, with agricultural soils representing a major source of contamination for overlying crops and grazing livestock. Understanding the prevalence and behaviour of pathogens in these soils is fundamental to ascertaining and mitigating the risk of disease from agroecosystems. This article reviews research pertaining to the overall distribution and abundance of clostridial pathogens in the soil while identifying possible environmental and soil factors influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 177 publications
(282 reference statements)
0
11
0
Order By: Relevance
“…Regarding conditions associated with C botulinum detection in poultry manure, this study shows that C botulinum was detected significantly more frequently at lower temperatures (28.1°C vs 38.7°C) and more frequently on the surface, with a mean temperature of 21.1°C vs 44.2°C deeper in the pile. The optimal growth temperature for C botulinum is between 30°C and 42°C, although it can survive between 10°C and 48°C 30 depending on the BoNT types and C botulinum group. The mean temperature measured at a depth of around 50 cm is most frequently within this interval and could allow the initiation of spore germination.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding conditions associated with C botulinum detection in poultry manure, this study shows that C botulinum was detected significantly more frequently at lower temperatures (28.1°C vs 38.7°C) and more frequently on the surface, with a mean temperature of 21.1°C vs 44.2°C deeper in the pile. The optimal growth temperature for C botulinum is between 30°C and 42°C, although it can survive between 10°C and 48°C 30 depending on the BoNT types and C botulinum group. The mean temperature measured at a depth of around 50 cm is most frequently within this interval and could allow the initiation of spore germination.…”
Section: Discussionmentioning
confidence: 99%
“…The contamination of susceptible birds and the initiation of a “carcass-maggot” amplifying cycle can lead to the development of outbreaks of botulism in the avifauna ( Wobeser, 1997 ; Soos and Wobeser, 2006 ). Type E, mainly identified in the northernmost regions of the northern hemisphere, is closely associated with aquatic, marine or freshwater ecosystems ( Dolman, 1957 ; Haagsma, 1991 ; Horowitz, 2010 ; Espelund and Klaveness, 2014 ; Palmer et al, 2019 ). Carriage by fish is most often intestinal ( Bott et al, 1966 , 1968 ; Yule et al, 2006 ); the contamination can lead to mortality in certain species more sensitive to toxin E. The disease can also spread to aquatic or coastal birds (fish-eating birds in particular), sometimes causing the death of thousands of individuals ( EPA, 2013 ).…”
Section: Clostridium Botulinum and Its Environmentmentioning
confidence: 99%
“…Clostridium is a genus of bacteria that causes a number of human diseases including botulism, gas gangrene and tetanus. Palmer et al () investigated the distribution and abundance of clostridial pathogens in soil as well as environmental and soil factors that might influence the bacteria's behaviour. Clostridial pathogens have been documented in soils worldwide, and the amendment of soil with manure and organic wastes was identified as a major route of bacteria introduction to the soil.…”
Section: Special Section Contentsmentioning
confidence: 99%
“…The incorporation of modern molecular and sequencing techniques into future studies was also recommended. Palmer et al () concluded that understanding clostridial pathogen amount, distribution and behaviour in soil was important because agricultural soil is the first control point in the food contamination pathway.…”
Section: Special Section Contentsmentioning
confidence: 99%